The Role Of Advertising In Public Life And The Concept Of Advertising Text - Nigora Makhmudova (Universitas Muhammadiyah Sidoarjo, 2022)
The article discusses the role of advertising in public life and the concept of advertising text. Currently, there are different approaches to clarifying the term